C-H•••O, C-H•••? and ?-? interactions in three benzofuran-2-yl ketone derivatives - Yilmaz, VT; Kazak, C; Kirilmis, C; Koca, M; Heinemann, FW (Blackwell Publishing, 2005)
The molecules of 2-benzoyl-1-benzofuran, C15H10O2, ( I), interact through double C - H center dot center dot center dot O hydrogen bonds, forming dimers that are further linked by C - H center dot center dot center dot O, C - H center dot center dot center dot pi and pi-pi interactions, resulting in a three-dimensional supramolecular network. The dihedral angle between the benzoyl and benzofuran fragments in ( I) is 46.15 ( 3) degrees. The molecules of bis(5-bromo-1-benzofuran-2-yl) ketone, C17H8Br2O3, (II), exhibit C-2 symmetry, with the carbonyl group (C=O) lying along the twofold rotation axis, and are linked by a combination of C - H center dot center dot center dot O and C - H center dot center dot center dot pi interactions and Br center dot center dot center dot Br contacts to form sheets. The stability of the molecular packing in 3-mesityl-3-methylcyclobutyl 3-methylnaphtho[1,2-b] furan-2-yl ketone, C28H28O2, (III), arises from C - H center dot center dot center dot pi and pi-pi stacking interactions. The fused naphthofuran moiety in ( III) is essentially planar and makes a dihedral angle of 81.61 ( 3)degrees with the mean plane of the trimethylbenzene ring.
Keywords: Furan